Drug Design Progress of In silico, In vitro and In vivo Researches - Qifeng, Bai; Lanlan, Li; Shanhui, Liu; Shujun, Xiao; Yu, Guo (Journal of In-vitro In-vivo In-silico Journal, 2018)
Drug design, referred to the fields of pharmacology, biotechnology and medicine, is in silico, in vitro and in vivo assay processes of finding new candidate medications based on the biological targets. The in silicoexperiments of drug discovery are involved in the macromolecular structure databases, small molecule databases, molecular docking, de novo drug design and molecular dynamics simulations. The in vitro experiments of drug discovery need evaluate the direct interaction information between ligands and targets as well as the function of ligands on signaling pathway in the cell. The in vivo experiments of drug discovery give the convincing evidence for preclinical trial at the physiological level. In this review, we outline the drug design components of databases, virtual screening tools, biochemical assays, cell-based system and animal models.
Keywords: virtual screening tools; biochemical assays; cell-based system and animal models